Potential Synergy Mechanism of Processing Methods for the Basic Remedies of Qixue Shuangbu Prescription Based on Integrated Metabolomics Strategy and Network Pharmacology Study. (10th May 2021) - Chen, Linwei; Sun, Xiaojun; Wang, Qin; Wu, Wenjun; Tian, Hu; Liu, Lunyuan; Jiang, Yong; Bei, Chenqi; Chen, Nan; Chen, Jing
Abstract: Qixue Shuangbu Prescription (QSP) is a famous traditional Chinese medicine (TCM) formula widely used for the treatment of chronic heart failure (CHF). Previous clinical studies have found that the efficacy of processed QSP has been significantly enhanced in the treatment of CHF. However, the synergistic mechanisms of processed QSP to enhance the treatment of CHF are still unclear. Generally, the changes in clinical effects mainly result from the variations of inside chemical basis caused by the TCM processing procedure. In this study, we developed a network pharmacology-integrated metabolomics strategy to clarify the difference of the effective compounds between crude and processed QSP, and further explain the mechanism of processed QSP to produce a synergistic effects. As a result, 69 different compounds were successfully screened, identified, quantified and verified as the most potential marker compounds. These different chemical components may play an anti-CHF and enhance the therapeutic effect through 52 action pathways such as estrogen signaling pathway, ubiquitin mediated proteolysis, protein processing in endoplasmic reticulum, etc. This study revealed that the proposed network pharmacology-integrated metabolomics strategy was a powerful tool for explaining the mechanism of synergistic action in the processing of QSP, further controlling the quality and understanding the processing mechanism of TCM formulae.